(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
This study aims to know and clarify the role played by the green tax on pollutants that is imposed to reduce environmental costs, because of its special importance, which is (the impact of imposing a green tax on pollutants that are harmful to the environment in reducing environmental costs is one of the goals that the financial authorities seek in order to increase Its relative importance in general, and in particular, reducing costs, including environmental costs. The study was processed by studying and analyzing the data obtained and discussing the results of the study, so that it was concluded that Iraqi legislation regarding green tax legislation was not taken into account, noting that there is a law regarding green tax in developed countries (developing countries), as it is noted when imposing This type of tax will reduce environmental costs and then increase revenues, including tax revenues on the one hand and preserving the environment from polluters on the other hand.